Wunderlich syndrome: a rare case in a young woman - Paparella, Maria Teresa; Eusebi, Laura; Gangai, Ilaria; Bartelli, Francesco; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2021)
We report the case of a 29-year-old woman with Wunderlich syndrome, a rare spontaneous renal hemorrhage into the subcapsular and perinephric space. She presented to our emergency department with a sudden and persistent right flank pain in the abscence of abdominal injury. The onset of the symptoms can be insidious and lead to hypovolemic shock. Computed Tomography helps both in the diagnosis, detecting the renal hemorrhage, and contributes to an optimal patient management. Selective arterial embolisation is an efficient technique to stop acute and potential life-threatening hemorrhage and preserve the renal parenchyma.